New recommendations for thromboelastography reference ranges for pregnant women - Polak, Ferdinand; Kolnikova, Ivana; Lips, Michal; Parizek, Antonin; Blaha, Jan; Stritesky, Martin (Thrombosis research, 2011)
INTRODUCTION: The target of this study was to compare thromboelastography coagulation parameters in pregnant and non-pregnant women. If appropriate, we would propose recommendations for new reference ranges for pregnant women in their third trimester. MATERIALS AND METHODS: Prospective observational study, comparing, by using thromboelastography, the blood samples of 60 healthy women in third trimester of pregnancy (group GRAV) to the samples of the control group of 43 healthy non-pregnant fertile women (group NON-GRAV). Selective percentiles were used to determine new reference limits. RESULTS: Mean values and standard deviations (SD) in both groups were as follows (GRAV vs NON-GRAV): time r 4.7 min (SD 1.7) vs. 7.8 (SD 2.8); time k1.5 min (SD 0.5) vs. 2,7 (SD 0,9); alpha angle 69.6° (SD 5.5) vs. 54.4 (SD 11.5); maximum amplitude 71.3mm (SD 4.5) vs. 63.1 (SD 5.4); coagulation index 2.7 (SD 1.8) vs. -1.9 (SD 3.0); LY60 1.1% (SD 1.8) vs. 4.8 (SD 3.6). Due to statistically significant differences between both groups, we established, based on our results, these new thromboelastography reference limits for pregnant women: time r 2-8 min ("common" range 4-8 min), time k 1-3 min ("common" range 1-4 min), alpha angle 60-77° ("common" range 47-74°), maximum amplitude 64-76 mm ("common" range 55-73 mm), LY60 0-3% ("common" range 0-15%), coagulation index 0-5 ("common" range (-3) - (+3)). CONCLUSIONS: It may not be suitable to use the same reference ranges for pregnant women as for the general population. Therefore, we suggest new reference limits for thromboelastography in pregnant women.
Keywords: tromboelastografie; těhotenství; Česká republika; studie případů a kontrol; Prospective Studies; Adult; Czech Republic; referenční hodnoty; ženské pohlaví; Thrombelastography; Humans; prospektivní studie; Reference Values; Pregnancy; třetí trimestr těhotenství; Pregnancy Trimester, Third; Blood Coagulation; dospělí; Female; hemokoagulace; lidé; Case-Control Studies